Investigation of Rain Effect on MIMO Systems at Microwave and Millimeter wave bands - Kirubel, Abiyu (ASTU, 2019)
The rapid growth of bandwidth, data rate and availability requirements is pushing for deployment of new schemes that can meet these requirement. MIMO systems deployment in microwave and millimeter wave bands looks to be a hugely promising approach in this regard. However, these spectra are highly affected by precipitation phenomena. So, it is imperative to deal with the performance limits of MIMO systems under rain, the principal degradation mechanism in these ranges of frequency and the dominant precipitation mechanism in Ethiopia. In the process of assessing the effect of rain on millimeter and microwave MIMO systems, the research work has tried to model the 1-minute integration time rain fall rate statistics of various locations in Ethiopia based on as much information as it was possible to gather locally. The deficiency of some widely used rain rate prediction approaches in relation to Ethiopia??s climate has been shown. Hence, a new improved rain rate integration time conversion method, based on 1-minute rain rate data from Jimma, has been used with good results. New R0.01 value for Jimma, Bahirdar, Addis Ababa and Mekele were calculated as 122.9, 130.49, 71.8 and 74.64 mm/h. In relation to this the worst-case rain cell size has been calculated. The distribution of rain drops, which are the agents of attenuation and scattering effects of rain, has been researched. Drop size distribution models have been compared for use in the research work for some locations in Ethiopia. The inaccuracy of models devised for temperate region of the world, which ITU uses for global attenuation prediction, has been shown. Tropical drop size distribution models, which better represent locations within Ethiopia than temperate models, have been used for attenuation calculation and determination of the propagation parameters; extinction, absorption, scattering coefficient and the anisotropy factor. In line with that new specific attenuation values are calculated based on adapted drop size distribution models. As large as 20dB/Km of difference was found between ITU's prediction and local data. The effect of rain on MIMO link capacity has been investigated. The system capacity performance has been compared under different scenarios. It has been shown that, while system performance like attenuation degrading system capacity increase with rain rate, there are circumstances where rain can also cause enhancements to capacity. It is demonstrated that these xvi rain rates, described as ??best rate?? rates, differ for varying distribution models and the signal to noise ratio of the link. Finally, the research concludes by indicating future research areas related to this research work. The field of study could be fine-tuned by furthering the study on variability of rain rate along a signal path (spatial distribution of rain rate), effect of non-sphericity of rain drops and effect of